Social Marketing Campaign in Tobacco Cessation to Young Adults - Adhianty Nurjanah, Yeni Rosilawati,; Sugiyo, Dianita; Nurmandi, Achmad; Habib, Shahid (Opción)
This study will evaluate the social marketing strategy to influence young adults by taking a case study in Klungkung Regency in Bali Province, Indonesia. This research specifically interested in looking at the social marketing strategy including channel analysis, market segmentation and audience analysis, considerations of product, price, place and promotions), implementation and evaluation of Tobacco Control Behavior. The study found that the social marketing using 4P (Product, Price, Place and Promotions) +additional 2P (Partnership and Policy) elements of social marketing. The product is the idea of healthy life, preventing is more worthy than cure. The price is the change of behaviour, from smoking to quit smoking, and to prevent the early smokers. The distribution channel is family and community support. The partnership is using community elements, among others,community leaders starting from Banjar (village), PKK (Family Welfare Program) mothers, Posyandu (Integrated Service Post) cadres and religious leaders. Finally the policy is the local regulations (Perda)Number 10 of 2011 concerning Smoke Free Area.